LATE VARISCAN POST-COLLISIONAL CU-NI SULFIDE DEPOSITS IN EAST TIANSHAN AND ALTAY IN CHINA: PRINCIPAL CHARACTERISTICS AND POSSIBLE RELATIONSHIP WITH MANTLE PLUME - Mao J.; Zhang Z.; Yang J.; Zhang C.; Pirajno F.; Chai F.; Wu H.; Cheng S.; Chen S. (My University, 2006)
In the past twenty years 18 Cu - Ni sulfide deposits and occurrences were discovered in the Chinese Tianshan and Altay orogenic belts in northern Xinjiang, China. There are several belts and ore districts along several parallel deep faults. The Kelatongke and several other Cu - Ni mineralized intrusions are located along the Etrix fault, which separates the Altay orogenic belt and Junggar Basin. The Huangshan, Huangshandong, Xiangshanq, Tudun, Erhongwa, Tula'ergen and Hongling deposits distribute along the Kanggurtag suture, which separates the Qol Tag orogenic belt and Turpan - Hami Basin. The Baishiquan, Tianyu, and Tianxiang deposits are located along the Aqikkuduk fault, which separates the Qol Tag orogenic belt and Middle Tianshan Precambrian terrane. The Poyi, Poshi and Luodong deposits are located along the Hongliuhe fault, which separates the Middle Tianshan Precambrian terrane and the Baishan Variscan rift. Re-Os dating for Cu - Ni sulfide ores reveals that the various ore belts formed in a small age range of 298-282 Ma. This age range is almost identical to the ages of related intrusions and dikes dated by the SHRIMP U-Pb zircon method. Tectonic and geochronological studies explain that the amalgamation of continental blocks mainly occurred during the Late Carboniferous in the Central Asian Orogenic Belt. Large-scale metallogenesis in this region was developed during post-collisional tectonism in the latest Carboniferous to Early Permian. The Cu - Ni sulfide deposits are one component of this large-scale metallogenesis. The Cu - Ni sulfide deposits in northern Xinjiang can be divided into: (1) magma conduit type and (2) differentiated sill type. Some mafic - ultramafic systems exhibit lithological zoning caused by strong differentiation. Stratiform ore bodies are hosted by ultramafic rocks at the base of the magma chamber. Good examples are provided by the Kelatongke, Huangshandong and Poshi deposits. Others, such as the Xiangshan, Baishiquan, Tianyu, and Tula'ergen deposits, are hosted by magma conduits consisting of peridotite, troctolite and pyroxenite. These ultramafic rocks either occur within faults or are surrounded by slightly younger diorite intrusions. These two types of orthomagmatic Cu - Ni sulfide deposits are also distributed along the same ore belts. For instance, the differentiated sill-related Huangshandong coexists with the magma conduit type of the Tula'ergen deposit in the Qol Tag orogenic belt. Orthomagmatic Cu - Ni sulfide deposits in northern Xinjiang were formed during post-collisional extensional tectonism and possibly related to a Late Carboniferous - Early Permian mantle plume event. The mafic - ultramafic systems and associated Cu - Ni deposits are commonly accompanied by dike swarms and are characterized by elongated outcrops developed along several parallel regional faults. These mafic - ultramafic systems and accompanying dikes are generally fractionated, hinting that they were feeders of now eroded flood basalts.
Keywords: ALTAY; CU-NI SULFIDE DEPOSIT; MANTLE PLUME; POST-COLLISION; TIANSHAN; XINJIANG; Палеозой::Пермская; Палеозой::Каменноугольная; Палеозой::Кембрийская; Paleozoic::Permian; Paleozoic::Carboniferous; Paleozoic::Cambrian